The Application of and Strategy for Gold Nanoparticles in Cancer Immunotherapy - He, Jia-shuai; Liu, Shi-jin; Zhang, Yi-ran; Chu, Xiao-dong; Lin, Zheng-bin; Zhao, Zhan; Qiu, Sheng-hui; Guo, Yan-guan; Ding, Hui; Pan, Yun-long; Pan, Jing-hua (Frontiers in Pharmacology, 2021)
Cancer immunotherapy is a validated and crucial approach for treating patients with cancer. It is a novel anticancer strategy that activates the immune system to recognize and kill cancer cells in patients. However, immunotherapy still faces many challenges in view of clinical efficacy and safety issues. Various nanomaterials, especially gold nanoparticles (AuNPs), have been developed not only for anticancer treatment but also for delivering antitumor drugs or combining other treatment strategies. Recently, some studies have focused on AuNPs for enhancing cancer immunotherapy. In this review, we summarized the application of AuNPs as immune agents, drug carriers or combinations with other immunotherapies for anticancer treatment. AuNPs can not only act as immune regulators but also deliver immune drugs for cancer. Therefore, AuNPs are candidates for enhancing the efficiency and safety of cancer immunotherapy.